New Security Risk Value Estimate Method for Android Applications. (14th November 2019) - Er-rajy, Latifa; El Kiram, My Ahmed; El Ghazouani, Mohamed
Abstract: Nowadays, mobile applications are the devices' core, so their security is essential for the platform on which are installed. Therefore, to make this security strong, Android implements permission system and sandboxing mechanism to reduce the attacks contingency. Also, antivirus software is used to detect the already known malware based on their signature, but unfortunately, this kind of program cannot detect cloned or repackaged malware. Thus, using authorizations to estimate the security vulnerability will surely be very useful for avoiding applications that are more susceptible to be dangerous according to the risk values obtained. Consequently, this will provide systematic support that will make it easier for users to make appropriate decisions and therefore greatly improve the Android devices' security. In this article, additionally to the risk measures that have been already proposed in previous studies based on functionalities such as permissions and function calls, we add a set of mathematical metrics describing the case of susceptible and innocent applications already known. Our risk assessment exploits applications already known as malware and safe samples without any threat.